RELATIONSHIP OF PERSONALITY TRAITS AND WORK SUITABILITY IN THE EMERGENCY AND TRAUMA DEPARTMENT AMONG ASSISTANT MEDICAL OFFICERS - Abu Samah Shukor; Nurul-Azza Abdullah (UIN Sunan Kalijaga, 2020)
Abstract. Medical staff assistants working in emergency and trauma departments must have appropriate traits in terms of personality traits to enable them to cope with stressful and stressful work and the best quality of work. Therefore, researchers have undertaken a study of the relationship between personality traits and work suitability in the emergency and trauma department. Data obtained by using a questionnaire form to obtain demographic data, personality data, job satisfaction data and job performance data. The questionnaire was distributed to 63 respondents consisting of medical staff assistants who work in the emergency and trauma department of two major hospitals in Perak. In the inference test, the results of the Pearson correlation showed a significant relationship between personality traits and job satisfaction with a coefficient of r = -.698 and p <.05. Meanwhile, personality traits were also found to be negatively related to tenure where the correlation coefficient was r = -702 and p <.05. In addition, the linear regression test conducted to see the effect of personality traits on work performance also showed that personality traits had a strong influence on work performance with a value of r = 0.473 and a significant p <0.05. The results of this study will assist supervisors and organizations in the recruitment process of medical personnel with appropriate personality traits to work in the emergency and trauma department.Keywords: Assistant medical personnel, emergency and traumadepartment, personality traits, job satisfaction, tenure, work performance Abstrak. Asisten staf medis yang bekerja di bagian gawat darurat dan trauma harus memiliki ciri-ciri yang sesuai untuk memungkinkan mereka mengatasi pekerjaan yang penuh tekanan dan stres serta kualitas kerja yang terbaik. Oleh karena itu, peneliti telah melakukan studi tentang hubungan antara ciri-ciri kepribadian dan kesesuaian kerja di bagian gawat darurat dan trauma. Data diperoleh dengan menggunakan formulir kuesioner untuk memperoleh data demografi, data kepribadian, data kepuasan kerja dan data prestasi kerja. Kuesioner dibagikan kepada 63 responden yang terdiri dari asisten staf medis yang bekerja di bagian gawat darurat dan trauma di dua rumah sakit besar di Perak. Pada uji inferensi hasil korelasi pearson menunjukkan adanya hubungan yang signifikan antara ciri kepribadian dengan kepuasan kerja dengan koefisien r = -.698 dan p <.05. Sedangkan ciri-ciri kepribadian juga ditemukan berhubungan negatif dengan masa kerja dimana nilai koefisien korelasinya adalah r = -702 dan p <.05. Selain itu, uji regresi linier yang dilakukan untuk melihat pengaruh ciri-ciri kepribadian terhadap prestasi kerja juga menunjukkan bahwa ciri-ciri kepribadian berpengaruh kuat terhadap prestasi kerja dengan nilai r = 0,473 dan signifikan p <0,05. Hasil penelitian ini akan membantu supervisor dan organisasi dalam proses perekrutan tenaga medis yang memiliki ciri kepribadian yang sesuai bekerja di bagian gawat darurat dan trauma.Kata kunci. Asisten petugas medis, bagian gawat darurat dan trauma, ciri kepribadian, kepuasan kerja, masa kerja, prestasi kerja